2023
DOI: 10.3389/fnagi.2022.933453
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of color vision and pupillary light responses in age-related macular degeneration

Abstract: IntroductionAge-related macular degeneration (AMD) is the leading cause of irreversible central vision loss in developed countries and one of the leading causes of blindness. In this work, we evaluated color vision and the pupil light reflex (PLR) to assess visual function in patients with early and neovascular AMD (NVAMD) compared with the control group.MethodsWe recruited 34 early patients with dry AMD and classified them into two groups following AREDS: 13 patients with NVAMD and 24 healthy controls. Contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Vemela et al [6] stated that both YB and RG types of CVD were significantly more prevalent in AMD patients compared to healthy people of the same age; the mentioned study uses Color Assessment and Diagnostic Test and relates these defects to choroidal hypoxia and changes in the function of retinal cells. Also, Decleva et al [33] in their study found that with using Cambridge Color Test, color vision defects are seen in all three axes of protan, deutan and triran in patients with AMD. Failure to identify YB defects by the Ishihara test is the most important reason for the difference in the results of the present study compared to other studies in this field.…”
Section: Discussionmentioning
confidence: 94%
“…Vemela et al [6] stated that both YB and RG types of CVD were significantly more prevalent in AMD patients compared to healthy people of the same age; the mentioned study uses Color Assessment and Diagnostic Test and relates these defects to choroidal hypoxia and changes in the function of retinal cells. Also, Decleva et al [33] in their study found that with using Cambridge Color Test, color vision defects are seen in all three axes of protan, deutan and triran in patients with AMD. Failure to identify YB defects by the Ishihara test is the most important reason for the difference in the results of the present study compared to other studies in this field.…”
Section: Discussionmentioning
confidence: 94%
“…SCN receives photoperiodic information from intrinsic photosensitive retinal ganglionic cells (ipRGCs) in retina, through the retinal-hypothalamic pathway, and subsequently regulates the sleep-awake cycle of human body ( Crislip et al, 2021 ). Decleva et al (2022) reported the impaired pupil light reflex (PLR) and function of ipRGCs in patients with early and neovascular AMD. Similarly, Maynard et al (2017) found the dysfunction of ipRGCs in patients with advanced AMD.…”
Section: Discussionmentioning
confidence: 99%